In silico trials of food digestion and absorption: how far are we?. (February 2020) - Le Feunteun, Steven; Mackie, Alan Robert; Dupont, Didier
Abstract : In recent years, experimental research on the mechanisms of food digestion in the gastrointestinal tract has strengthened our knowledge on the effect of food on human health. A number of mathematical models have been proposed to rationalize our understanding on the related mechanisms. One common suggestion is that in silico models could be interconnected and used in the future to predict the effect of food systems (liquid or solid, inner microstructure, state of nutrients…) on various metabolic responses. This paper aims to provide a brief overview of the latest developments in this young but promising field of research.